Estudo de retrofit de microusinas fotovoltaicas para integração de sistemas de armazenamento de energia por baterias - Maia, Weliton da (2024)
Solar photovoltaic energy has shown intense growth in the last decade between 2013 and 2023. Data from global renewable energy reports show a record increase of 407 GW in 2023 alone, reaching 1,589 GW of installed capacity. Brazil has also shown significant growth with more than 50 GW by December 2024. This advance has driven interest in solutions that integrate grid-connected photovoltaic systems (GCPV) with battery energy storage. This combination offers benefits such as improved grid quality and reliability, demand management, and greater energy security through backup systems. Currently in Brazil, there is no specific standard to address the application of GCPV with batteries, however some laws and standards tend to influence the use of these systems in the country, such as Law 14300, REN No. 1000/2021, and INMETRO Ordinance 140 of 2022. This study aimed to study and propose retrofit solutions for photovoltaic micro-power plants, exploring different ways of integrating batteries with existing systems. The methodology adopted involved a detailed literature review and analysis of the technological solutions available on the market, focusing on the equipment and configurations used in different scenarios. Based on this information, integration strategies were developed, including the case study in Green Office at the Federal Technological University of Paraná, evaluating nine different configurations, which include replacements and couplings of inverters. The results obtained confirmed the viability of the proposed solutions, demonstrating that micro-power plants can be modernized efficiently, with significant gains in operational flexibility and energy efficiency. It was also demonstrated that for a retrofit to be successful, it is necessary to validate a series of items, including the final objective of the application and the need for modifications to the electrical infrastructure of the site. In addition, the proposed solutions contribute to increasing the energy autonomy of users and reducing operational costs. In the case of the Green Office, it was found that the best retrofit option would be scenario 5, which uses an AC-coupled inverter, since it does not replace the university’s operating inverter, it would be less costly to implement, and it would allow for all possible services. Overall, this work represents an important contribution to the Brazilian photovoltaic sector, by offering practical and technical subsidies that can guide future initiatives for integrating GCPV with battery storage systems, promoting sustainability and technological advancement in the field of renewable energy.